Community Policing Philosophy - Meini, Bruno (Journal of Contemporary Sociological Issues, 2024)
A sociological understanding of crime can adequately respond to criminal challenges through practical engagement with society. Community policing is a proactive strategy that uses problem-solving methods and strategic partnerships to solve problems related to public safety, including crime and social disturbance. The core of this policing system is a flexible organizational structure and decentralized power, in which the officer decides how best to preserve security and order in line with local needs. Decentralized administration at both the command and decision-making levels has been used as an approach to promote the effectiveness of community policy. Consequently, police officers could independently interact with communities, identifying problems and developing feasible solutions. However, this idea has variations, particularly in the debate on how community policy can construct a social system to create better strategies against criminal acts. It is essential to analyze the sociological perspective to understand the main objective of the community-oriented policing strategy. Mainly, a theory that focuses on reducing crime and crime fear enhances the conditions of life for law enforcement personnel and members of society. Hence, this article analyses each strategy component using pertinent and specific sociological theories and criminological concepts, highlighting the significant contribution of sociologists in shaping the community policing strategy. Therefore, based on sociological perspectives, this article argues that community policy can create an inclusive social system within social actors’ collaboration. Keywords: community-oriented, crime, neighborhood, sociological perspective, partnerships